Nutritional Quality of Rice Variety in Sabah, Malaysia - Neoh, Wei Ting; Lum, Mok Sam (e-VIBS, Faculty of Science and Natural Resources, 2018)
Five rice samples collected in Sabah (white, red, black, brown and aroma rice) were evaluated for protein content and nutritional quality. Protein content of the rice samples obtained ranged from 13.13 to 24.60%. Mineral contents were significantly higher in brown rice than the others The phosphorus (P), sodium (Na), potassium (K), magnesium (mg) and copper (Cu) contents ranged from 3.48 to 4.28, 19.95 to 27.60, 74.98 to 627.17, 68.40 to 126.73 and 0.57 to 1.63 mg/100 g, respectively among the rice samples. The lowest contents of these elements were observed in white rice. Traditional rice varieties found in Sabah have better nutritional quality than white rice due to much more availability of minerals. These rice varieties may be utilized in rice breeding for specific grain quality.